Optimal design of a nuclear power plant condenser control system based on multi-objective optimization algorithm - Zhi, Chen; Li, Yiliang; Ke, Huang; Kai, Xiao (Nuclear technology & radiation protection, 2020)
A condenser control system of a nuclear power plant consists of a pressure control system, a condensate water sub-cooling degree control system and a water level control system. The existing control optimization methods can hardly take into account all the performance indices of the three control systems at the same time. To solve this problem, this paper presents a control optimization method based on a multi-objective optimization algorithm. This method takes control parameters as optimization objects, and takes the performance of step response as optimization objectives. The multi-objective particle swarm optimization algorithm based on Pareto dominance concept is used to solve the optimization problem. This enables obtaining of high-quality control parameters. Simulation results confirm the feasibility and effectiveness of this control optimization method. nema